2017
DOI: 10.24925/turjaf.v5i4.388-396.1172
|View full text |Cite
|
Sign up to set email alerts
|

Sivas İlindeki Bazı Süt İşletmelerine Gelen Sütlerin Fiziksel, Kimyasal ve Mikrobiyolojik Özelliklerinin Belirlenmesi

Abstract: Bu araştırmada Sivas ilinde bulunan 5 süt fabrikasının depo tankından temin edilen 50 adet süt örneğinin fiziksel, kimyasal ve mikrobiyolojik özellikleri belirlenmeye çalışılmıştır. Araştırma sonucunda süt örneklerinin pH, asitlik derecesi (%), yağ, yağsız kurumadde, toplam kurumadde ve yoğunluk değerlerinin sırasıyla 4, 89-6,70, %0,135-0,495, %1,7-7,6, %7,33-9,80, %10,00-16,90, 1,0230-1,0312 g/mL arasında değiştiği ve süt örneklerinin hepsinin fosfataz pozitif olduğu saptanmıştır. Elde edilen veriler Türk Gıd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…They found that the highest coliform group bacteria count was 5.9 cfu/mL. The high levels of coliform group bacteria in raw milk was stated to indicate that hygiene precautions were not taken during and after milking, and the tools and equipment used for milking were not sufficiently cleaned and necessary care was not taken about cleaning [19,29]. There is no standard for dry matter amounts included in the Turkish Food Codex Communiqué on Raw Milk and Heat Treated Drinking Milk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They found that the highest coliform group bacteria count was 5.9 cfu/mL. The high levels of coliform group bacteria in raw milk was stated to indicate that hygiene precautions were not taken during and after milking, and the tools and equipment used for milking were not sufficiently cleaned and necessary care was not taken about cleaning [19,29]. There is no standard for dry matter amounts included in the Turkish Food Codex Communiqué on Raw Milk and Heat Treated Drinking Milk.…”
Section: Discussionmentioning
confidence: 99%
“…If not, the bacteria in milk transform lactose to lactic acid, increasing the acidity and lowering the pH. As this situation causes milk to clot, it makes it difficult or even impossible to obtain products from raw milk [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The employment created for each country is the key to the balance of rural development and agriculture, especially in terms of the value of the domestic and export markets it creates. Dairy products take an important place in these markets (Beykaya et al 2017). About 18 million tonnes of milk are produced annually in Turkey.…”
Section: Introductionmentioning
confidence: 99%